Diastolic dysfunction is associated with exercise impairment in patients with sickle cell anemia. Issue 8 (21st May 2018) - Alsaied, Tarek; Niss, Omar; Powell, Adam W.; Fleck, Robert J.; Cnota, James F.; Chin, Clifford; Malik, Punam; Quinn, Charles T.; Taylor, Michael D.
Abstract: Background: Left ventricular diastolic dysfunction (DD) is an independent risk factor for mortality in sickle cell anemia (SCA) and is associated with increased extracellular volume (ECV) on cardiac MRI (CMR). Exercise impairment is common in SCA, but its causes and prognostic value are not well understood. Objective: To study the effects of DD and ECV on cardiopulmonary exercise test (CPET) in patients with SCA. Methods and Results: As part of a prospective study to characterize the cardiomyopathy of SCA (NCT02410811), 20 children and adults with SCA underwent CMR, echocardiography, and cycle ergometer CPET (age range 8–43 years). Maximum exercise was reached in 18 patients and 17 (94%) had reduced exercise capacity (%predicted VO2 less than 80%). Six patients had DD and none had systolic dysfunction. Patients with DD had lower exercise capacity compared to patients with normal diastolic function (%predicted VO2 48.2 ± 9.1% vs. 61.2 ± 11.7%; P  = 0.01). The z‐score of left ventricular lateral E/e' ratio, which is a marker of DD, was negatively associated with %predicted VO2 (r = −0.61, P  = 0.01). All patients with moderate‐to‐severe exercise impairment (%predicted VO2  < 60%) had lateral E/e' z‐score > 2. In a multivariate analysis, lateral E/e' z‐score was independently associated with %predicted VO2 ( P  = 0.02). All participants had elevated ECV but the degree of elevation was not associated with exercise parameters. Conclusion: Left ventricular DD is associated with decreased exercise capacity in SCA. Interventions to prevent or delay DD could improve exercise capacity, quality of life, and long‐term outcomes in SCA.